Effect of long-chain omega-3 polyunsaturated fatty acids on cardiometabolic factors in children with acute lymphoblastic leukemia undergoing treatment: a secondary analysis of a randomized controlled trial - Barbosa-Cortes, Lourdes; Atilano-Miguel, Salvador; Martin-Trejo, Jorge Alfonso; Jiménez-Aguayo, Emmanuel; Martínez-Becerril, Fabian Ismael; López-Alarcón, Mardia; Mejía Aranguré, Juan Manuel; Maldonado-Hernández, Jorge; Delgadillo-Portillo, Suyly; Guzmán-Castro, Brenda; Delgadillo-Portillo, Jazmín; Añoveros-Barrera, Ana; et al. (Frontiers in Endocrinology, 2023)
Introduction Increased triglycerides (TGs) are a major risk factor for cardiovascular disease. Furthermore, hypertriglyceridemia is commonly associated with a reduction of high-density lipoprotein cholesterol (HDL-C) and an increase in atherogenic small-dense low-density lipoprotein (LDL-C) levels. Studies provide support that polyunsaturated omega-3 fatty acids (ω3-LCPUFAs) are cardioprotective and have antithrombotic and anti-inflammatory effects. The potential effects of ω3-LCPUFAs on cardiometabolic factors and anti-inflammatory actions in children with acute lymphoblastic leukemia (ALL) are limited. This is a secondary analysis of a previous clinical trial registered at clinical trials.gov (# NCT01051154) that was conducted to analyze the effect of ω3-LCPUFAs in pediatric patients with ALL who were receiving treatment. Objective: To examine the effect of supplementation with ω3-LCPUFAs on cardiometabolic factors in children with ALL undergoing treatment. Methods Thirty-four children (placebo group: 20 patients; ω3-LCPUFAs group: 14 patients) aged 6.7 ± 2.7 years who were newly diagnosed with ALL were evaluated. Children were randomized to receive either ω3-LCPUFAs or placebo capsules (sunflower oil). ω3-LCPUFAs were administered in the form of 500-mg soft capsules. The ω3-LCPUFA capsules contained 225 mg of DHA, 45 mg of EPA, and 20 mg of another ω3-LCPUFAs. The omega-3 dose was administered at a rate of 0.100 g/kg of body weight/day for three months. Main outcomes: Fasting cholesterol, HDL-C, very-low-density lipoprotein (VLDL-C), TGs, atherogenic index of plasma (AIP), android/gynoid ratio (A/GR), IL-6, TNF-α, and percentage of fat mass (DXA) were measured in all patients. Fatty acid analyses in red blood cells were performed with gas chromatography. Results We found significantly lower levels of TGs (p=0.043), VLDL-C (p=0.039), IL-6 (p=0.025), and AIP (p=0.042) in the ω3-LCPUFAs group than in the placebo group at three months. In contrast, the total cholesterol concentration was higher at 3 months in the ω3-LCPUFAs group than in the placebo group (155 mg/dl vs. 129 mg/dl, p=0.009). The number of children with hypertriglyceridemia (85% vs. 50%; p=0.054) tended to be lower between the time of diagnosis and after 3 months of supplementation with ω3-LCPUFAs. Conclusion These findings support the use of ω3-LCPUFAs to reduce some adverse cardiometabolic and inflammatory risk factors in children with ALL. Clinical trial registration ClinicalTrials.gov, identifier NCT01051154.